THE DISCRIMINATION UNDER THE PRINCIPLE OF NATIONAL TREATMENT UNDER THE GATT AND THE GATS: DE FACTO OR DE JURE DISCRIMINATION - Mahfud, Mahfud (Indonesian Journal of International Law, 2014)
Both the GATT and the GATS provisions have the same points of view on defining discrimination as an unequal treatment given to foreign providers compared to treatment given to domestic providers. Discrimination under the national treatment of the GATT and the GATS is considered as a practice that prevents foreign providers from enjoying all comfortable facilities that are given to domestic providers. Non-discriminatory application in both provisions might also be interpreted in the market access issue. Moreover, it is not considered as discrimination of national treatment of both provisions if it concerns on laws, regulations, or requirement regulating the procurement by government agencies. Both provisions use likeness and treatment no less favourable test in order to determine whether or not there is a discrimination against foreign products or services or services suppliers. There are several distinctions of discriminations between the principle of national treatment under the GATT and the GATS. The discrimination under the principle of national treatment of the GATT has general application to all trade in goods. On the other hand, the discrimination under national treatment obligation for trade in services under the GATS only applies if commitments have been scheduled. It can be concluded that the discrimination of national treatment under the GATT and the GATS seems to be de facto discrimination because both provisions do not provide the sufficient measures in order to find a violation. It results from; the GATS national treatment is derived from traditional concepts of the GATT that the application of the national treatment of the GATT is adduced by the GATS.